In silico Analysis of the Potential of Red Betel (Piper crocatum) Active Compounds as Anti-Inflammatory Drug Candidate - Zainul Aziz, R. Ahmad; Purnama, Erlix Rakhmad (LenteraBio : Berkala Ilmiah Biologi, 2024)
Inflammation is the body's response to tissue damage, but if uncontrolled, it can become pathological. Piper crocatum, commonly known as red betel, has long been recognized for its health benefits, yet scientific research on its active compounds remains limited. This study aims to predict the anti-inflammatory potential of red betel leaf's active compounds against pro-inflammatory proteins. Using an in silico molecular docking approach, this research targeted the TNF-? and TACE as a target receptor macromolecule. The processes of exploration, screening, docking, and visualization were conducted using RCSB PDB, PubChem, ADME Calculator, AutoDock, and Biovia Discovery Studio. The findings revealed that none of the active compounds from red betel leaves exhibited lower binding affinity values than the native ligand for the TNF-? protein. However, one compound showed a lower binding affinity compared to the native ligand for the TACE protein and demonstrated binding capability to the HIS 415 amino acid. Consequently, no red betel leaf compounds are predicted to be potential anti-inflammatory agents for inhibiting TNF-? activity. In contrast, one active compound from red betel leaves, 2(2-isopropyl-5-methylphenoxy)-N2-(4-carboxybenzylidene), displayed predicted potential for inhibiting TACE protein activity.